2015
DOI: 10.1039/c4ta03144j
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of Co-doped Zn2SnO4–graphene–carbon nanocomposites with improved lithium storage performances

Abstract: Co-doped Zn 2 SnO 4 -graphene-carbon nanocomposites have been prepared for the first time through a convenient one-step hydrothermal method. The size of Co-doped Zn 2 SnO 4 nanoparticles is about 3-5 nm and they are well dispersed on graphene nanosheets and carbon layer. L-Ascorbic acid is introduced to serve as a reductant for GO and carbon sources. The doping of Co can enhance the crystalline degree of Zn 2 SnO 4 nanoparticles. When evaluated as anode materials for lithium ion batteries, the Co-ZTO-G-C nanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In particular, cationic doping has been considered as another effective strategy to improve electrical conductivity and charge transfer ability and thus enhance the electrochemical performance of metal oxide anode materials. [31][32][33][34][35][36] Until now, different metal cations have been incorporated into the lattice of a variety of metal oxides to improve the electrochemical performance. For instance, Cu cation doping can increase the specic capacity from 361 mA h g À1 of Mn 2 O 3 to 642 mA h g À1 of Cu-doped Mn 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, cationic doping has been considered as another effective strategy to improve electrical conductivity and charge transfer ability and thus enhance the electrochemical performance of metal oxide anode materials. [31][32][33][34][35][36] Until now, different metal cations have been incorporated into the lattice of a variety of metal oxides to improve the electrochemical performance. For instance, Cu cation doping can increase the specic capacity from 361 mA h g À1 of Mn 2 O 3 to 642 mA h g À1 of Cu-doped Mn 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…34 Recently, it has been reported that Co doping in Zn 2 SnO 4 can greatly enhance the cycle stability and rate capability. 35 On the other hand, most of the conventional LIB anodes usually use polymers and carbon black as binders, which may experience virtual swelling in commonly used electrolytes, leading to a rapid capacity degradation, poor cycle stability and rate capability. 31 The polymer and carbon black additives generate a weight increase (10-40%) in battery electrodes and extra steps to mix and combine those materials into a lm form.…”
Section: Introductionmentioning
confidence: 99%
“…23 To date, intensive efforts have been devoted to preparing graphene-based transition metal oxide composites, which exhibit great improvements in their electrochemical performance of high lithium storage capability. [24][25][26][27] Compared with two-dimensional (2D) graphene, three-dimensional (3D) graphene aerogels (GAs) have attracted considerably more attention due to their unique 3D interconnected framework, high surface area, fast mass and electron transport rate and good flexibility. 28 Therefore, it is still desirable to develop a simple method to achieve 3D hierarchical CoFe 2 O 4 /GAs composites with a longer cycling life and higher rate performance.…”
Section: Introductionmentioning
confidence: 99%
“…A number of research groups also suggested the partial contribution of these reactions. 30,34,[36][37][38] Our value is less than the theoretical capacity (1231 mA h g -1 ) of mechanism "B". The remaining portion of the crystalline α-and β-Sn phase could be evidence for an incomplete alloying reaction.…”
Section: Resultsmentioning
confidence: 99%